Categorisation of disease severity states in fibromyalgia: a first step to support decision-making in health care policy - Salaffi, Fausto; Di Carlo, Marco; Arcà, Silvia; Galeazzi, Mauro (Clinical and experimental rheumatology, 2018)
To establish the cut-off points for disease severity states of two self-administered questionnaires (the revised version of the Fibromyalgia-Impact Questionnaire [FIQR] and the Fibromyalgia Assessment Status [FAS]) designed for the evaluation of multidimensional aspects of fibromyalgia (FM). In this cross-sectional study, consecutive FM patients completed both FIQR and FAS. The external criterion for grading disease severity was the item one of the Short Form-36 Health Survey (SF-36). The reconciliation approach of the 75th-25th percentiles of adjacent ranks was applied to establish cut-off points distinguishing between disease activity states. 521 FM patients (80.0% women, mean age 49 years) completed the assessment. The overall mean (standard deviation [SD]) FIQR and FAS were 47.87 (SD 20.69) and 5.57 (SD 2.09), respectively. The highest FIQR scored items were those related to sleep quality, fatigue/energy, pain, stiffness, tenderness, and environmental sensitivity. With the reconciliation of 75th-25th percentiles of adjacent ranks, the FIQR cut-off points obtained were: remission ≤30, mild severity >30 and ≤45, moderate severity >46 and ≤65, high severity >65. The same approach for FAS leaded to: remission ≤4, mild severity >4 and ≤5.5, moderate severity >5.6 and ≤7.0, high severity >7.0. The majority of the subjects was classified as suffering from a moderate (FIQR 28.4%; FAS 23.2%) or severe (FIQR 24.4%; FAS 30.7%) FM. The FIQR and FAS cut-off points for remission, mild, moderate and high disease severity are valid measures which can be easily applied in daily clinical practice.